Exploring Identity: If Your Soul Could Speak, What Would She Say? - Gombert, Debra Jelinek (Voices: A World Forum for Music Therapy, 2017)
This Arts Based pilot focuses on the author’s explorations in music, movement, painting, and words, as she engaged in a self-inquiry into voice and identity. It has been suggested that such reflexive inquiry is necessary so that researchers and clinicians understand their own intersectional and shifting identities before they engage with another person’s identities. In order to know what social justice is, we must first understand our own identity. The author used art for self-inquiry as both the method and a way of knowing. She analyzed her process and art through writing, and finally by making a video, with the intention that the resultant video would show enough of the process/result that it could stand on its own. The author shares a link to the resultant video and some of the artwork produced, as well as her context and methods for the project. The paper and video culminate with an invitation to the reader to engage in a similar reflexive process, asking for a response to the prompt “Exploring identity: What would you say?”